Accuracy and Usefulness of Select Methods for Assessing Complete Collection of 24‐Hour Urine: A Systematic Review. Issue 5 (3rd January 2016) - John, Katherine A.; Cogswell, Mary E.; Campbell, Norm R.; Nowson, Caryl A.; Legetic, Branka; Hennis, Anselm J. M.; Patel, Sheena M.
Abstract : Twenty‐four–hour urine collection is the recommended method for estimating sodium intake. To investigate the strengths and limitations of methods used to assess completion of 24‐hour urine collection, the authors systematically reviewed the literature on the accuracy and usefulness of methods vs para‐aminobenzoic acid (PABA) recovery (referent). The percentage of incomplete collections, based on PABA, was 6% to 47% (n=8 studies). The sensitivity and specificity for identifying incomplete collection using creatinine criteria (n=4 studies) was 6% to 63% and 57% to 99.7%, respectively. The most sensitive method for removing incomplete collections was a creatinine index <0.7. In pooled analysis (≥2 studies), mean urine creatinine excretion and volume were higher among participants with complete collection ( P <.05); whereas, self‐reported collection time did not differ by completion status. Compared with participants with incomplete collection, mean 24‐hour sodium excretion was 19.6 mmol higher (n=1781 specimens, 5 studies) in patients with complete collection. Sodium excretion may be underestimated by inclusion of incomplete 24‐hour urine collections. None of the current approaches reliably assess completion of 24‐hour urine collection.